Financial Reporting Excellence: Synergy of Good Governance, Human Resources, and Utilization of Information Technology - Egi Gumala Sari; Jihan Maharani; Hamdan (Balance Vocation Accounting Journal, 2026)
This study focuses on the Financial Reporting Quality of companies in the Infrastructure Sector, while most of the previous studies examined the Financial Reporting Quality in the government enviroment. This study uses a quantitive approach. This research was conducted using a questionnaire distributed to 130 financial managers working in 130 companies in the Bekasi and Cikarang Industrial Areas. To get the result of this study, researchers uses PLS SEM Version 3.0. This study shows that Good Corporate Governance has a positive but statistically insignificant impact on Financial Reporting Quality. Human Resources Competencies also has a positive but not statistically significant effet on the Financial Reporting Quality. Information Technology Utilization does not strengthen the relationship between Good Corporate Governance and Financial Reporting Quality, nor does it strengthen the relationship beetwen Human Resources Competencies and Financial Reporting Quality.This study has several limitations in its measurement method. All variables, such as Good Corporate Governance and Human Resource Competencies as the dependent variable, and Information Technology Utilization as a moderating variable, are measured using a questionnaire. Thus, the data obtained only reflects the preceptions of respondents.